Strategies for Improving Medical Personnel Resilience in Facing Catastrophic Emergencies at Patar Asih Hospital, Lubuk Pakam, in 2023 - Herryaanto Lumbantobing (Medistra Medical Journal (MMJ), 2025)
Catastrophic emergencies, such as natural disasters, mass accidents, and pandemics, demand high preparedness and resilience from medical personnel in hospitals. This study aims to identify the resilience level of medical staff at RSU Patar Asih Lubuk Pakam and to formulate strategies to enhance resilience in facing catastrophic emergency situations in 2023. The research method employed a mixed-methods approach with a descriptive-analytical design. Quantitative data were collected using the Connor-Davidson Resilience Scale (CD-RISC) questionnaire administered to 120 medical personnel selected through stratified sampling. Qualitative data were obtained through in-depth interviews with 10 key informants from various hospital units. The results indicate that the majority of medical personnel have a moderate level of resilience (50%), with an average score of 28.5 out of a maximum of 40. Factors significantly influencing resilience are social support (β=0.381; p<0.01), self-efficacy (β=0.295; p<0.01), and workload (β=-0.271; p=0.015). The strategies implemented mostly focus on technical aspects, while psychosocial elements and disaster simulations remain inadequate. In-depth interviews revealed an urgent need for disaster SOPs, coping mechanism training, and psychological support for medical personnel. The study recommends a multilevel approach that includes enhancing individual capabilities, strengthening team support and organizational culture, as well as developing crisis management policies and SOPs integrated with psychosocial services. This strategy is expected to improve the resilience and preparedness of medical personnel in effectively and sustainably facing catastrophic emergencies.